Learning Application Through Visual Media to Enhance Senses for Early Childhood Based on Multimedia at Dahlia Kindergarten - Pratama, Gelard Untirtha; Permana, Basuki Rakhim Setya; Auliana, Sigit; Sunardi, Sunardi; Arrasit, Dio Falla (ARRUS Journal of Engineering and Technology, 2024)
With the rapid advancement of information technology, there has been an overflow of dynamically flowing data without limits and regardless of time. Perhaps one thing we must not forget is that data can be communicated with the help of images. One of the most popular learning methods today is sensory perception learning media. The analysis used is to study a number of information about sensory perception learning and collect materials related to sensory perception that will be used in this application program. Such as searching and editing images. The aim is to help beginners learn about sensory perception so that it can provide convenience in learning, without having to adjust the time of learning. Then an application program was made to recognize sensory perception. Sensory perception learning through this learning media is a useful media for helping to recognize sensory perception, through sensory perception learning media this makes an interesting and effective thing because it is designed with images, animations, and sounds that support the atmosphere of learning.